Do We Really Need Ribavirin in the Treatment of Crimean-Congo Hemorrhagic Fever?*. (June 2014) - Kalın, Gamze; Metan, Gökhan; Demiraslan, Hayati; Doganay, Mehmet
Abstract : The role of ribavirin in the treatment of Crimean-Congo hemorrhagic fever (CCHF) is scarce. We retrospectively reviewed treatment features of 81 hospitalized patients with laboratory confirmed CCHF between January 2007 and December 2010. The median age of the patients was 45 years and 47 were male. Out of 81 patients, 6 received ribavirin. Demographic characteristics and laboratory findings of the patients who received ribavirin were not different from the patients who did not receive antiviral. There were no statistically significant difference in duration of symptoms before admission ( P = 0·47) between the two groups. Of the patients, 29 who did not receive ribavirin and four from the ribavirin treated group had severe disease based on the Swanpoel criteria ( P = 0·22). Two patients from each group died. There was no statistically significant difference in case fatality ( P = 0·14) and duration of hospitalization ( P = 0·11). Treatment of CCHF without ribavirin seems to be safe based on the findings of this study.